The Effect of Salary and Work Environment on Employee Performance of PT Win Access Telecommunication Banjarmasin - Nur Halifah; Teguh Wicaksono; Fanlia Adiprimadana Sanjaya (International Forum of Researchers and Lecturers, 2025)
At PT Win Access Telecommunication Banjarmasin, the target-based salary system that drives performance actually causes stress and dissatisfaction due to the imbalance of compensation and a less supportive work environment, which has a negative impact on motivation, productivity, and stability of the company, so a comprehensive assessment is needed to create optimal working conditions according to the needs of employees and the organization. The objectives of this study are to: 1) Determine and test the effect of salary on employee performance at PT Win Access Telecommunication Banjarmasin; 2) Determine and test the effect of the work environment on employee performance at PT Win Access Telecommunication Banjarmasin, and; 3) Determine and test the effect of salary and work environment on employee performance at PT Win Access Telecommunication Banjarmasin. This quantitative study examines the effect of salary and work environment on employee performance at PT Win Access Telecommunication Banjarmasin in March-June 2025 with a sample of 84 out of 509 employees using a Likert scale questionnaire, data were analyzed through descriptive statistics, validity tests, reliability, classical assumptions, multiple linear regression, and partial and simultaneous hypothesis tests to determine the relationship between variables significantly. The results of this study are: 1) There is a significant influence between Salary partially on the performance of PT Win Access Telecommunication Banjarmasin; 2) There is a significant influence between Work Environment partially on the performance of PT Win Access Telecommunication Banjarmasin), and; 3) There is a significant influence between salary and work environment simultaneously on the performance of PT Win Access Telecommunication Banjarmasin.